How Can Nursing Teams Respond to Large-Scale COVID-19 Screening? - Zhao, Huihan; He, Yu; Brister, Fang; Yang, Li; Li, Gaoye; Ling, Ying; Ying, Yanping (Frontiers in Public Health, 2021)
The COVID-19 virus has devastated lives and economies worldwide. The responses of nursing teams to large-scale COVID-19 screening have rarely been addressed or described. The aim of this study is to introduce an efficient response strategy for nurses in large-scale COVID-19 screening. A new COVID-19 case was confirmed on Jan 14, 2021 in Nanning, China. Immediately, a large-scale COVID-19 screening was launched and ran from Jan 14 to Jan 17, 2021. Our nurse team responding to the screening included 3 major components: 1) establishing a leadership group and a nucleic acid sampling emergency team; 2) defining, conducting, and evaluating nurse training; 3) implementing efficient sampling schemes (10 in 1 mixed sample technique). A total of 500 nurse volunteers were recruited and divided into three echelons. A total of 353 trained nurses were sent to 65 sampling stand stations. In cooperation with nurses from other health institutions, samples were collected from a total of 854,215 people in only 4 days for 2019-nCOV nucleic acid screening. The preparation and efficient response strategies used to conduct this screening may provide a baseline reference for future large-scale COVID-19 screening worldwide.